Characterization of the Sos Enattos site for the Einstein Telescope. (February 2020) - Naticchioni, L; Boschi, V; Calloni, E; Capello, M; Cardini, A; Carpinelli, M; Cuccuru, S; D'Ambrosio, M; de Rosa, R; Di Giovanni, M; d'Urso, D; Fiori, I; et al.
Abstract: In this work we report the ongoing characterization of the Sos Enattos former mine (Sardinia, Italy), one of the two candidate sites for the Einstein Telescope (ET), the European third-generation underground interferometric detector of Gravitational Waves. The Sos Enattos site lies on a crystalline basement, made of rocks with good geomechanical properties, characterized by negligible groundwater. In addition, the site has a very low seismic background noise due to the absence of active tectonics involving Sardinia. Finally, the area has a low population density, resulting in a reduced anthropic noise even at the ground level. This location was already studied in 2012-2014 as a promising site for an underground detector. More recently, in March 2019, we deployed a new network of surface and underground seismometers at the site, that is currently monitoring the local seismic noise. Most of the energy carried by the seismic waves is due to the microseisms below 1 Hz, showing a significant correlation with the waves of the west Mediterranean sea. Above 1 Hz the seismic noise in the underground levels of the mine approaches the Peterson's low noise model. Exploiting mine blasting works into the former mine, we were also able to perform active seismic measurements to evaluate the seismic waves propagation across the area. In conclusion we also give a first assessment about the acoustic and magnetic noise in this underground site.